A new rapid neutron activation analysis system at Dalat nuclear research reactor - H., V. Doanh; C., D. Vu; T., Q. Thien; P., N. Son; N., T. Sy; N. , Giang; N., N. Dien (Nuclear Science and Technology, 2014)
An auto-pneumatic transfer system has been installed at the Dalat research reactor for rapid instrument neutron activation analysis based on very short-lived nuclides. This system can be used to perform short irradiations in seconds either in the vertical channel 13-2 or in the horizontal thermal column of the reactor. The transferring time of sample from irradiation to measurement position is approximately 3.2 seconds. A loss-free counting system using HPGE detector has been also setup in compacting with the pneumatic transfer system for measurement of sample’s activity, automatically starting for data acquisition at irradiated sample’s arrival. This new facility was tested and shown to have high potential for the determination of short-lived nuclides with half-lives from 10 ¸ 100 seconds. This work presents the results of timing parameter measurements, characterization of irradiation facilities, and application of this system to determining Selenium concentration in several biological reference materials.